Molecular characterization of SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) gene family from Citrus and the effect of fruit load on their expression - Shalom, Liron; Shlizerman, Lyudmila; Zur, Naftali; Doron-Faigenboim, Adi; Blumwald, Eduardo; Sadka, Avi (Frontiers in Plant Science, 2015)
We recently identified a Citrus gene encoding SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) transcription factor that contained a sequence complementary to miR156. Genes of the SPL family are known to play a role in flowering regulation and phase transition. In Citrus, the mRNA levels of the gene were significantly altered by fruit load in buds; under heavy fruit load (ON-Crop trees), known to suppress next year flowering, the mRNA levels were down-regulated, while fruit removal (de-fruiting), inducing next-year flowering, resulted in its up-regulation. In the current work, we set on to study the function of the gene. We showed that the Citrus SPL was able promote flowering independently of photoperiod in Arabidopsis, while miR156 repressed its flowering-promoting activity. In order to find out if fruit load affected the expression of additional genes of the SPL family, we identified and classified all SPL members in the Citrus genome, and studied their seasonal expression patterns in buds and leaves, and in response to de-fruiting. Results showed that two additional SPL-like genes and miR172, known to be induced by SPLs in Arabidopsis, were altered by fruit load. The relationships between these factors in relation to the fruit-load effect on Citrus flowering are discussed.